Association between environmental lead/cadmium co-exposure in drinking water and soil and type 2 diabetes mellitus/obesity in Southern China - Qu, Zhi; Zhou, Jianli; Guo, Peisen; Wang, Jingrui; Wang, Panpan; Liu, Limin; Wu, Mengdi; Wang, Peixi; Liu, Nan (Frontiers in Public Health, 2022)
Lead (Pb) and cadmium (Cd) in environment can be directly absorbed by drinking water and soil. However, data on human Pb and Cd exposure by drinking water and soil and its long-term consequence for type 2 diabetes mellitus (T2DM) and obesity are lacking. Our study aims to explore the association of typical heavy metals co-exposure in drinking water and soil to the community residents with T2DM and obesity indices in two cities of southern China. A cross-sectional study enrolling total 1,274 participants was performed and the local water and soil samples were collected in two communities in southern China. The average daily dose (ADD) of heavy metals was calculated to assess the exposure. The obesity indices comprise body mass index (BMI), waist-to-hip ratio (WHR) and waist circumference (WC). Binary, multiple logistic and linear regressions were employed for assessing the associations of Pb and Cd exposure with T2DM and obesity. The results showed that there weren't any significant correlations between ADDs of Pb/Cd and T2DM in community residents (all Ps>0.05). Compared with those with 18.5 ≤ BMI <24, with 1 μg/kg bw/d ADD of Pb increase in exposure are associated with 49.2–56.1% lower likelihood of overweight. Besides, with ADDs of Pb exposure was increased by 1 μg/kg bw/d and WHR decreasing by 0.01–0.02, and WC decreasing by 2.22–4.67 cm. We speculate that Pb causes weight loss because it damages the absorption function of the gastrointestinal tract as an initial injury. 1μg/kg bw/d ADD of Cd increase is associated with 100.9% upper likelihood of low weight in Model 1. It suggests that Pb/Cd pollution in the local environment was serious and harmful to residents' health. Government should introduce relevant oversight and accountability systems to improve the prevention and management of lifestyle-related chronic diseases in the future.